2018
DOI: 10.1111/jcmm.13558
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA BDNF‐AS inhibits proliferation, migration, invasion and EMT in oesophageal cancer cells by targeting miR‐214

Abstract: This study was aimed at exploring the effect of lncRNA BDNF‐AS on cell proliferation, migration, invasion and epithelial‐to‐mesenchymal transition (EMT) of oesophageal cancer (EC) cells. The expression of BDNF‐AS and miR‐214 in tissue samples and cells was measured by qRT‐PCR. The targeted relationship between BDNF‐AS and miR‐214 was analysed by dual‐luciferase reporter assay. After cell transfection, the cell proliferation activity was assessed by MTS method, while the migrating and invading abilities were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…These branched CDH1 + tubules in 2D cultures are more likely to represent ureteric bud derivatives and inhibiting miR-214-3p could, thus, favor ureteric bud epithelium stabilization, while restricting MM (as shown by the reduction in WT1 + cells). In agreement with this interpretation, CDH1 itself has been previously reported as a direct target of miR-214 ( Wang et al., 2016 ), while in some cancers miR-214 was found to promote EMT ( Liu et al., 2018a ; Long et al., 2015 ; Zhao et al., 2018 ) and therefore inhibiting it would be expected to result in epithelial stabilization.…”
Section: Discussionsupporting
confidence: 75%
“…These branched CDH1 + tubules in 2D cultures are more likely to represent ureteric bud derivatives and inhibiting miR-214-3p could, thus, favor ureteric bud epithelium stabilization, while restricting MM (as shown by the reduction in WT1 + cells). In agreement with this interpretation, CDH1 itself has been previously reported as a direct target of miR-214 ( Wang et al., 2016 ), while in some cancers miR-214 was found to promote EMT ( Liu et al., 2018a ; Long et al., 2015 ; Zhao et al., 2018 ) and therefore inhibiting it would be expected to result in epithelial stabilization.…”
Section: Discussionsupporting
confidence: 75%
“…Several lines of evidence suggested that lncRNA BDNF‐AS was remarkably downregulated in a variety of tumour cells with its level of expression being correlated with cancer aggressiveness and inhibited tumorigenesis by regulating cell proliferation, migration, invasion, and apoptosis. For example, lncRNA BDNF‐AS was significantly decreased in oesophageal cancer tissues and cells; besides, lncRNA BDNF‐AS upregulation reduced oesophageal cancer cell proliferation, migration, and invasion as well as epithelial‐to‐mesenchymal transition (EMT) . Forced expression of lncRNA BDNF‐AS in human retinoblastoma cells inhibited cell proliferation and migration and induced cell‐cycle arrest .…”
Section: Discussionmentioning
confidence: 62%
“…Recent studies have shown that the EMT program is closely linked to tumor metastasis. 35,36 Notably, EMT markers, including E-cad (marker of epithelial cells), N-cad and VIM (markers of mesenchymal cells), are regulated by the ERK1/2 signaling pathway in pancreatic cancer. [37][38][39][40] In the current study, we indicated that ApoE2 activated ERK1/2 signaling to promote the expression of N-cad and VIM at both the mRNA and protein levels while reducing the expression of E-cad.…”
Section: Discussionmentioning
confidence: 99%